Five Nights at Freddy's : Fazbear Frights - Vol 2 graphic novel collection. Vol. 2 - Cawthon, Scott, 1971-; Hastings, Chris, 1983-; Waggener, Andrea Rains, 1960-; West, Carly Anne; Esmeralda, Didi; Morris, Anthony, Jr.; MacPherson, Coryn; De la Cruz, Eva; Sawyer, Benjamin; Duarte, Gonzalo (Colorist); Myers, Micah (New York : Graphix, an imprint of Scholastic, 2023)
"Oscar, ever the miniature grown-up his mom needs him to be, decides to take something he wants... even though he knows its wrong. Stanley is newly dumped, stuck in a dead -end job for a mysterious employer, and unable to connect with anyone. And Devon, abandoned by his dad and ignored by his mom, cant understand why love and friendship come so easily to everyone except him. Unfortunately, in the callous world of Five Nights at Freddys, its always in the depths of loneliness when evil creeps in." --Back cover.
New kid.
Keywords: Interpersonal relations -- Comic books, strips, etc; Loneliness -- Comic books, strips, etc; Pizzerias -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Horror comics; Comics adaptations; Graphic novels